Unconstrained melting inside a sphere - Hosseinizadeh, S. F. (2013)
This paper presents both numerical and experimental investigations on unconstrained melting of phase change material (PCM) using n-octadecane inside a spherical container. Experimental studies are performed for three different wall temperatures of the container at 35 °C, 40 °C and 45 °C with the PCM at an initial sub-cooling of 1 °C below the melting temperature. Numerical simulations are performed for axisymmetric melting of PCM inside a sphere using the Fluent 6.3 software. After validating the numerical results with the experimental data, the effect of shell diameter on melting at different Stefan numbers is studied numerically. The results indicate that the melting rate is high at the beginning of melting due to perfect contact between the hot shell and solid PCM. The melting rate reduces with progressing time when a layer of molten PCM is formed between the shell and solid PCM. After this stage, the effect of conduction heat transfer diminishes and restricted to the bottom of sphere where the solid PCM sinks. At both sides of the sphere, convection heat transfer in the liquid PCM becomes the dominant mode for melting.